Lymphocyte Count and SARS-CoV-2 Antibody Level in Healthy Donors' Blood at an Indonesian Blood Transfusion Center - Prasasti, Adelia Gita; Woelansari, Evy Diah, Suhariyadi; Anggraini, Anita Dwi (Folia Medica Indonesiana, 2023)
Highlights: 1. It is essential to conduct research on SARS-CoV-2 for the purpose of acquiring further understanding, especially concerning the production of antibodies examined using antibody titer blood tests. 2. Although the relationship between the examined variables is not significant, this study offers valuable information on blood test results after the COVID-19 vaccination, which can serve as scientific evidence for further research. Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that infects the respiratory system by attacking the mucous and epithelial cells. This infection commonly leads to an increase in lymphocyte count as an immune response to invading pathogens. Moreover, antibodies bind and inactivate foreign substances to destroy pathogens and inhibit their replication. These mechanisms prompt the objective of this study, which was to define the relationship between lymphocyte count and SARS-CoV-2 antibody level. This analytical observational study used a cross-sectional approach with quantitative analysis methods and purposive sampling. Healthy donors who had received coronavirus disease (COVID-19) vaccines provided the samples for this study. A total of 30 blood samples were collected from the Blood Transfusion Center of the Indonesian Red Cross Surabaya Area. This study was conducted in May 2022 at two distinct locations. The examination of lymphocytes was carried out using the flow cytometry method in the Hematology Laboratory, Department of Medical Laboratory Technology, Politeknik Kesehatan Kemenkes Surabaya, Surabaya, Indonesia. In addition, the antibody titer test using the enzyme-linked immunosorbent assay (ELISA) method was performed in the Immunoserology Laboratory of the Surabaya Health Laboratory Center, Surabaya, Indonesia. The analysis revealed an average lymphocyte concentration of 2.2633 x 103/µl and an average antibody level of 0.2197 according to the optical density (OD) ratio. The data analysis was performed using Spearman's rank correlation statistical test (p<0.005), and the results indicated a lack of significance with p=0.262. In conclusion, there is no relationship between total lymphocyte count and SARS-CoV-2 antibody level.